A survey on tourism experiences by Hungarian travellers: towards guest satisfaction - Magyar, Márton (Applied Studies in Agribusiness and Commerce, 2013)
In the 21st century experiences got great significance in the every-day life and in tourism as well. Human popularity can achieve very good and happy moments e.g. by shopping (complex experience in shopping centres) by common spare time activities in the nature and in towns, also by having vacation at a special destination. Animation/entertainment is a sphere of hotel services that is to help the guests sparing their free time on holidays in a good atmosphere, by providing experienceful programs. Good memories of a tourism service can make guests satisfied and build a returning clientele sphere. That is why it is awaited to map the (potential) guests’ expectations and observations of services. This paper discusses Hungarian tourists’ experiences conducted in Hungary aiming to reveal the need for professional services focusing on the not-so-spread area, Animation. The experiential dimensions of every-day life and tourism was studied by an own-edited questionnaire (N = 1000) in the half-year period of 1st August 2010 – 31st January 2011. This study was extended by quality of life since summer 2011 and I am going to compare the results of these two surveys with the aim of development suggestions in order to achieve a main level of guest satisfaction and a loyal sphere of clientele.